The Eyes Know Time: A Novel Paradigm to Reveal the Development of Temporal Memory. Issue 2 (20th August 2013) - Pathman, Thanujeni; Ghetti, Simona
<x xml:space="preserve">Abstract</x> Temporal memory in 7‐year‐olds, 10‐year‐olds, and young adults (N = 78) was examined introducing a novel eye‐movement paradigm. Participants learned object sequences and were tested under three conditions: temporal order, temporal context, and recognition. Age‐related improvements in accuracy were found across conditions; accuracy in the temporal conditions was correlated with conventional time knowledge. Eye movements tracked the veridicality of temporal order memory in adults and 10‐year‐olds seconds before providing memory judgments, suggesting that these movements reflect implicit access to temporal information. Seven‐year‐olds overall did not show this eye‐movement effect, but those who did were more accurate than those who did not. Results suggest that eye movements capture aspects of temporal memory development that precede overt decision processes—with implications for hippocampal development.